EMU Journal of Pharmaceutical Sciences (EMU JPharmSci) Vol:3 No:1 (2020) - N/A (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
[Abstract Not Available]
EMU Journal of Pharmaceutical Sciences (EMU JPharmSci) is a peer reviewed, open access journal that is dedicated to any discipline under the category of pharmaceutical sciences. It publishes research articles, short communications, and reviews under the pharmacy discipline. These include pharmaceutical chemistry, biochemistry, pharmacognosy, pharmaceutical botany, microbiology, toxicology, the history of pharmacy and areas such as phytotherapy, ethnobotany, sports pharmacy, which have gained importance in recent years, are also included within the scope of the journal. The journal is aimed to be published for three times a year and the first volume is published on November 2018. The publication language is English. The aims of the journal are to contribute to the scientific development and advancement of researchers within the field of pharmacy and to allow the exchange of information among readers.
Keywords: Pharmaceutical Sciences; Pharmacy